PENGARUH MODAL, LOKASI DAN JAM KERJA TERHADAP TINGKAT PENDAPATAN PEDAGANG DI WISATA PANTAI SELATBARU KECAMATAN BANTAN DALAM PERSPEKTIF EKONOMI ISLAM - Novia Sari; Sandi Andika (Bertuah: Journal of Sharia and Islamic Economics, 2020)
Trade is the main root of national development and regional development, which aims to create an advanced and independent society and physically and mentally prosperous. The goal of traders is to get high income to meet their needs. Several factors that affect the level of income include capital, location and working hours. The purpose of this study was to determine the effect of capital, location and working hours on the income level of traders. A questionnaire in the form of a questionnaire was used to collect data. The total population of the study was all traders in Selatbaru Beach, which consisted of 40 people, all of whom were used as research samples. In analyzing data; Researchers used multiple linear regression quantitative analysis. Hypothesis testing using the t test shows that "the three independent variables studied were proven to have a significant partial effect on the dependent variable traders' income". Then through the F test it can be seen that "the three independent variables studied simultaneously affect the dependent variable, namely the income of traders". The Adjusted Square R2 figure of 0.767 shows that 76.7% of traders' income variables can be explained by the three independent variables in the regression equation. While the remaining 23.3% is explained by other variables outside the three variables used in this study.Key words: Capital; working hours; location; income; multiple regression analysis